Mobile Cellular Telephone: Fixed-Line Substitution in Sub-Saharan Africa - Esselaar, Steve; Stork, Christoph (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2005)
Mobile cellular telephones have been the success story of communications globally. In the developed world, mobile telephony is traditionally seen as being complementary to fixed-line telephony, primarily because of its pervasiveness but also because the fixed-line network provides access to other technologies such as broadband. This article finds that, in nine African countries, in contrast to the developed world, mobile telephony is a substitute for fixed-line telephony – across all income groups and not just low income households as previously thought. The article argues in addition that pre-paid payment options (not just for mobile phones) are key to increasing use by low income households because irregular incomes do not support regular financial commitments in terms of contracts.